Answer:
(14,-1)
Step-by-step explanation:
okay so first you need to use the "x=4y+10" in the first equation.
Rewrite as
3(4y+10) +11y=7
Distribute the 3(4y+10)
Rewrite as
12y+30
You'll have the equation
12y +30 +11y= 7
Subtract the 7 from both sides
12y+30+11y-7= 0
Combine like terms
23y+23=0
the best thing to do here is divide the equation by 23.
23/23 = 1
you'll have
y + 1 = 0
this simplifies to
y= -1
use this y value to solve for x
the easiest way to do this is start with the equation
x = 4y +10
Substitute the y for -1
x = -4(-1) +10
x = 4 +10
x = 14
the solution point is
(14,-1)
Answer:
1) not a function
2) Function
3) Function
Step-by-step explanation:
So in matt's equation, he made a mistake in the a transision from line 2 to line 3
in line 2: -4(-2)2
in line 3: -4(4)
the mistake is that -2 times 2 is not equal +4 it is equal to -4
also from lines 5 to 6 he made a mistake in order of opperations (mulit division then addition and subtract)
line 5: -10+30/5
line 6: 20/5
so he first subtracted 10 then divided, he should have divided then subtracted
so the equation should have equaled
Karen used the correct (-) times (+) property and the order of operations
so Karen is correct and Matt is wrong.